Repurchase Intention Analysis through Satisfaction and Trust of Shopee Users - Surahman, Surahman; Ariyanti, Ema Wahyuni; Maihan, Andhika Auliya; Lestari, Indriyani Dewi (International Journal Labs, 2021)
Background: Online business people or online sites in Indonesia are very rife, ranging from retail players who had been leading in offline businesses also switched to online, such as Matahari online, Alfamart, Indomart, and others. They compete with existing onlne businesses such as Shopee, Tokopedia, Bukalapak, Lazada, Blibli, JD.id, Orami, Bhineka and others. Aim: This study aims to identify the effect of influencing factors of repurchase intention through satisfaction and trust in users of online shopping Shopee. Method: A quantitative approach uses to run path analysis processed with IBM SPSS Statistic V 23 and Structural Equation Modeling (SEM) software with IBM AMOS V 5. The sample of 138 respondents were taken from ten sub-districts in Samarinda City. The measurement scale uses a likert scale with a score of 1 - 5. This study also tested the validity and reliability test, then carried out further test of estimation and structural fit model test. Findings: Based on structural model, it can be proven that experience and hedonic value have significant effect on satisfaction, website quality and privacy have significant effect on trust, trust have significant effect on satisfaction, website quality, privacy and satisfaction have significant effect on repurchase intention; website quality and privacy have significant effect on satisfaction, expeience and hedonic value have no significant effect on trust, experience, hedonic value and trust have no significant effect on repurchase intention.